Magnetic poly(2-hydroxyethyl methacrylate) microspheres for affinity purification of monospecific anti-p46 kDa/Myo1C antibodies for early diagnosis of multiple sclerosis patients. Issue 2 (28th April 2017) - Horák, Daniel; Hlídková, Helena; Kit, Yurii; Antonyuk, Volodymyr; Myronovsky, Severyn; Stoika, Rostyslav
Abstract : The aim of the present study is to develop new magnetic polymer microspheres with functional groups available for easy protein and antibody binding. Monodisperse macroporous poly(2-hydroxyethyl methacrylate) (PHEMA-COOH) microspheres ~4 µm in diameter and containing ∼1 mmol COOH/g were synthesized by multistep swelling polymerization of 2-hydroxyethyl methacrylate (HEMA), ethylene dimethacrylate (EDMA), and 2-[(methoxycarbonyl)methoxy]ethyl methacrylate (MCMEMA), which was followed by MCMEMA hydrolysis. The microspheres were rendered magnetic by precipitation of iron oxide inside the pores, which made them easily separable in a magnetic field. Properties of the resulting magnetic poly(2-hydroxyethyl methacrylate) (mgt.PHEMA) particles with COOH functionality were examined by scanning and transmission electron microscopy (SEM and TEM), static volumetric adsorption of helium and nitrogen, mercury porosimetry, Fourier transform infrared (FTIR) and atomic absorption spectroscopy (AAS), and elemental analysis. Mgt.PHEMA microspheres were coupled with p46/Myo1C protein purified from blood serum of multiple sclerosis (MS) patients, which enabled easy isolation of monospecific anti-p46/Myo1C immunoglobulin G (IgG) antibodies from crude antibody preparations of mouse blood serum. High efficiency of this approach was confirmed by SDS/PAGE, Western blot, and dot blot analyses. The newly developed mgt.PHEMA microspheres conjugated with a potential disease biomarker, p46/Myo1C protein, are thus a promising tool for affinity purification of antibodies, which can improve diagnosis and treatment of MS patients.